A repl . y to the sixth edition of a pamphlet (supposed official) on the state of the nation at the commencement of the year 1822; considered under the four departments of Finance, Foreign Relations, Home Department, Colonies, and Board of Trade, &c.&c. (Inserted in no. XXXIX. of the Pamphleteer) :; (The Pamphleteer, 1822)
The Pamphleteer ; vol. XXI, no. XLI, p. 3-41.